SOIL PHYSICAL ATTRIBUTES AND SOYBEAN ROOT GROWTH AFTER AUTUMN-WINTER CROPS - Ribeiro, L. M.; Flauzino, D. S.; Ceccon, G. (Revista Brasileira de Engenharia de Biossistemas, 2019)
Previous crops may modify soil physical conditions, crop development and yield. The objective was to evaluate soil physical attributes and root growth of soybeans after autumn-winter crops. The experiment was conducted in the experimental area of ​​Embrapa Agropecuária Oeste, in Dourados, MS, in a clayey dystroferric RED LATOSOLO. The experimental design was in randomized blocks with sub-divided plots, with four replications. In the plots were allocated four autumn-winter crops (Urochloa ruziziensis, corn intercropping with U. ruziziensis, single corn and cowpea (Vigna unguiculata)) and the subplots the two soybean cultivars BRS 284 and BRS 360 RR. Soil and root samples of soybean were collected at depths of 0.0 - 0.10 m; 0.10 - 0.20 m; 0.20 - 0.30 m; 0.30 - 0.40 m. The type of crop interfered in the physical quality of the soil. Cowpea and U. ruziziensis provided higher microporosity and total soil porosity; the corn intercropping with U. ruziziensis provided higher macroporosity and total soil porosity; the single corn increased in soil density, but the soybean showed higher root growth after U. ruziziensis.